Analisa Kebutuhan Instrumentasi Geoteknik Dry Dam Bendungan Sawangan Kabupaten Minahasa Utara - Farhan Zaky; Hari Nugroho; Sutarto Edhisono (Borneo Engineering : Jurnal Teknik Sipil, 2023)
Located in the downstream watershed, Manado city is at risk of hydrometeorological disasters such as flooding every year, especially in conjunction with high tides. One solution to the city's flooding problem is to provide flood water storage by building the Sawangan dry dam in North Minahasa Regency. In building a dam, dam safety is a very important requirement to minimize disaster risks for the community such as property losses and damage to infrastructure downstream of the dam. Dam safety is highly dependent on the accuracy of planning and during construction. The safety of a dam also depends on the operation stage, the implementation of maintenance, as well as intensive and continuous supervision, monitoring the behavior of the dam and its building facilities. The purpose of the geotechnical instrumentation analysis study of Sawangan Dam in North Minahasa Regency is to determine the ideal geotechnical instrumentation needs in the process of optimal and periodic observation of dam behavior. Geotechnical parameters affect dam behavior due to soil strength related to pore water pressure, water seepage, deformation characteristics of foundation and embankment materials during construction and after construction. Determination of the amount of geotechnical instrumentation installed at Sawangan Dam is based on technical data of the dam dimensions. Based on the analysis conducted, the required geotechnical instrumentation components are; pore water pressure gauges, dam deformation gauges installed inside and outside the embankment, groundwater level gauges, seepage gauges, reservoir water level gauges, and other supporting components. By installing geotechnical instrumentation using telemetry systems or integrated computer systems, data acquisition, management and security are easier.